MENDESAIN BANGSA YANG RELIGIUS DAN NASIONALIS DARI BANGKU SEKOLAH - Nanang Faisol Hadi (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
Character education is a major issue in the development of national education. Character education or character education plus is a necessity in the success of humans in the future. This research was conducted in order to look the forms of religious and nationalist education in school. The study was conducted by using the literature review method in the library with data collection techniques through reading various books as a comparison of opinions between several authors, then the reading results were analyzed through grouping and categorization, so that finally found the concept of religious character education and true nationalism. From the results of the study it is known that the concept of fostering religious character education and nationalism is carried out in an integrated manner through three main elements, namely educational support devices, intervention in character values into three components of education in schools, and habituation in the school environment. The values of Religious character and Nationalism that are developed are values related to divinity (relegius), character values related to oneself (honest, responsible, disciplined, hard work, curious, independent and love of science), related character values with others (polite, respecting the work of others, adhering to social rules and democracy), character values related to the environment (social and environmental care). The implementation of religious character and nationalism education is carried out by incorporating the values of religious character and nationalism into the syllabus and plans for learning devices